Microlearning untuk Mendukung Pembelajaran Mandiri Mahasiswa: A Systematic Literature Review - Safnowandi Safnowandi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of digital technology in higher education encourages a paradigm shift in learning towards student-centered learning and requires self-directed learning. One of the digital learning approaches that has developed to support this need is microlearning, which is a learning strategy that presents material in small, focused, flexible, and easily accessible units through various digital devices. This study aims to analyze the use of microlearning in supporting students' independent learning through the Systematic Literature Review (SLR) approach. The study process was carried out by referring to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 through the stages of identification, screening, feasibility evaluation, and article synthesis. The literature was obtained from various scientific databases with article criteria that discussed the implementation of microlearning in the context of higher education and its relevance to aspects of independent learning. A total of 30 articles published in the period 2016–2025 were analyzed using a thematic synthesis approach. The results of the study show that microlearning contributes positively to increasing learning motivation, self-regulated learning, student engagement, knowledge retention, learning outcomes, and students' ability to manage learning time. The implementation of microlearning generally uses media in the form of short videos, infographics, interactive quizzes, podcasts, and digital modules that are integrated with online learning platforms. However, the success of its implementation is influenced by the quality of instructional design, the digital competence of lecturers, the readiness of technological infrastructure, and integration with broader learning strategies. This study confirms that microlearning has the potential as an effective digital learning strategy to strengthen students' independent learning in higher education.